2007
DOI: 10.1038/oby.2007.591
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Assessment of Epicardial Adipose Tissue With Cardiovascular Magnetic Resonance Imaging

Abstract: Quantitative assessment of epicardial fat mass using the CMR-based volumetric approach is feasible and yields superior reproducibility compared with conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 23 publications
(28 reference statements)
6
141
1
16
Order By: Relevance
“…17,[19][20][21][22] Previous studies have shown that diabetic obese humans and rodents have elevated hepatic, myocellular and myocardial lipid content, and that treatment with pioglitazone leads to decreased hepatic and myocardial lipid together with improved insulin sensitivity. 23 Assessment of EF volume (EFV) and myocardial TG content (MTGC) has already been validated [24][25][26] with the emergence of non-invasive three-dimensional volumetric imaging techniques such as 3-T magnetic resonance imaging (MRI). This technique is also useful to address the relationship between excess myocardial lipids and impaired myocardial function.…”
Section: Introductionmentioning
confidence: 99%
“…17,[19][20][21][22] Previous studies have shown that diabetic obese humans and rodents have elevated hepatic, myocellular and myocardial lipid content, and that treatment with pioglitazone leads to decreased hepatic and myocardial lipid together with improved insulin sensitivity. 23 Assessment of EF volume (EFV) and myocardial TG content (MTGC) has already been validated [24][25][26] with the emergence of non-invasive three-dimensional volumetric imaging techniques such as 3-T magnetic resonance imaging (MRI). This technique is also useful to address the relationship between excess myocardial lipids and impaired myocardial function.…”
Section: Introductionmentioning
confidence: 99%
“…Gorter et al (19) docu-mented in a CT study that patients with high body mass index (>27 kg/m 2 ) have more EAT volume than those with a BMI <27 kg/m 2 . Both MRI and echocardiographic studies support that EAT strongly and independently reflect intra-abdominal visceral fat (18)(19)(20).…”
Section: Metabolic Syndromementioning
confidence: 83%
“…In addition, mean EFT can be calculated by averaging results from the long-axis and short-axis measurements. MRI also allows quantitative assessment of the amount of EAT at the end diastole in the short-axis views covering the entire left and right ventricle by using the modified Simpson's rule with integration over the image slices (20).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Furthermore there are substantial individual differences in pericardial fat distribution, therefore single point measurements used in echocardiography are unlikely to accurately quantify the absolute amount of fat. It was first shown by Fluechter et al that CMR measurement of epicardial fat volume is feasible, [22] and CMR has recently been validated in the assessment of pericardial adipose tissue volume in an ovine model showing a strong correlation between CMRderived paracardial adipose tissue volume and ex vivo paracardial fat mass [23]. The metabolically active epicardial fat, comparable to visceral fat deposits, is associated with cardiovascular disease, its risk factors and the metabolic syndrome [14,32] as well as with systemic markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[21] It has been shown that the assessment of the amount of epicardial fat assessed by a CMR-based volumetric approach is superior to conventional imaging techniques such as echocardiography [22] and accurately reflects pericardial adipose tissue mass [23].…”
Section: Introductionmentioning
confidence: 99%